Chemoproteomic identification of a DPP4 homolog in Bacteroides thetaiotaomicron - Keller, Laura J.; Nguyen, Taylor H.; Liu, Lawrence J.; Hurysz, Brianna M.; Lakemeyer, Markus; Guerra, Matteo; Gelsinger, Danielle J.; Chanin, Rachael; Ngo, Nhi; Lum, Kenneth M.; Faucher, Franco; Ipock, Phillip; et al. (Nature chemical biology, 2023)
Serine hydrolases have important roles in signaling and human metabolism, yet little is known about their functions in gut commensal bacteria. Using bioinformatics and chemoproteomics, we identify serine hydrolases in the gut commensal Bacteroides thetaiotaomicron that are specific to the Bacteroidetes phylum. Two are predicted homologs of the human dipeptidyl peptidase 4 (hDPP4), a key enzyme that regulates insulin signaling. Our functional studies reveal that BT4193 is a true homolog of hDPP4 that can be inhibited by FDA-approved type 2 diabetes medications targeting hDPP4, while the other is a misannotated proline-specific triaminopeptidase. We demonstrate that BT4193 is important for envelope integrity and that loss of BT4193 reduces B. thetaiotaomicron fitness during in vitro growth within a diverse community. However, neither function is dependent on BT4193 proteolytic activity, suggesting a scaffolding or signaling function for this bacterial protease. Bioinformatic and chemoproteomic approaches resulted in the identification of a homolog of human dipeptidyl peptidase 4 in the gut bacterium Bacteroides thetaiotaomicron that regulates envelope integrity and community fitness.